Influence of lymphadenectomy on survival and recurrence in patients with early-stage epithelial ovarian cancer: a meta-analysis - Chenchen Yang; Ting Zhang; Aifeng Gong; Can Shi (BMC, 2023)
Abstract Background This meta-analysis aimed to evaluate the effectiveness of lymphadenectomy on survival and recurrence in patients with early-stage epithelial ovarian cancer (eEOC). Methods Relevant studies were searched from four online databases. Hazard ratios (HRs) with 95% confidence intervals (CIs) or risk ratios (RRs) with 95% CIs were used to evaluate the effects of lymphadenectomy on overall survival (OS), progression-free survival (PFS), and recurrence rates. A subgroup analysis was performed to explore the sources of heterogeneity, followed by sensitivity and publication bias assessments. Results Fourteen articles involving 22,178 subjects were included. Meta-analysis revealed that lymphadenectomy was significantly associated with improved OS (HR = 0.72; 95% CI:0.61, 0.84; P < 0.001), improved PFS (HR = 0.74; 95% CI: 0.67, 0.80; P < 0.001), and reduced recurrence rates (RR = 0.72; 95% CI: 0.60, 0.85; P < 0.001). Subgroup analysis showed that factors including area, histology, and source of the control group were significantly related to improved OS and PFS in patients with eEOC. Sensitivity analysis showed that the combined results were stable and reliable, and no significant publication bias was observed. Conclusions Patients with eEOC can benefit from lymphadenectomy, with improved survival outcomes (OS and PFS) and a lower recurrence rate.